INTERVENTION TO INCREASE BREAST MILK PRODUCTION:LITERATURE REVIEW - Sukmawati Sukmawati; Aditya Nugraha; Agnes Dwi; Amiatun Amiatun; An Nisa Apriliani; Anggi Ramdani; Asep Nugraha; Tasya Puja Yarsita (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
Exclusive breastfeeding coverage in Indonesia is still below the National target. Breast milk is the best nutrition for babies and affects the growth and development of babies. One of the reasons for the low coverage of exclusive breastfeeding is the lack of milk production, so that various interventions are needed to increase milk production. This literature study aims to determine interventions to increase breast milk production. The research method uses Narrative Literature Review. The database used by Google Scholar, Pubmed, and Sciencedirect with the keywords Breast Milk